Comparison of Bioactive Compounds in Local and Imported Coriander Leaf Extracts Using GC-MS - Silfi Indrian; Alfi Asben; Kurnia Harlina Dewi (Green Engineering Society, 2026)
Coriander leaves contain bioactive compounds that are beneficial to health, but the content can differ depending on the origin and environmental conditions where they grow. Coriander leaves of local Indonesian or imported origin differ in their characteristics and bioactive compound content, necessitating analysis of both types. This study aims to analyse the bioactive compounds in the extract of local Indonesian coriander leaves from Bukittinggi, West Sumatra, and imported coriander from Egypt using gas chromatography–mass spectrometry (GC–MS). Coriander leaves were extracted using 96% ethanol in an ultrasonic bath. The extract was analysed for pH, antioxidant and antibacterial activity, residual ethanol content, and GC–MS to identify the compounds present. The results showed that the local Bukittinggi coriander leaf extract had a pH of 4.01, antioxidant activity based on DPPH inhibition of 88.34%, antibacterial activity against Staphylococcus aureus with a clear zone diameter of 23.38 mm, and a residual ethanol content of 0.68%. Meanwhile, the imported Egyptian coriander leaf extract had a pH of 3.68, antioxidant activity of 83.25%, antibacterial activity of 26.00 mm, and a residual ethanol content of 0.00%. Imported Egyptian coriander leaves exhibited higher antibacterial activity and lower residual ethanol content than local Bukittinggi coriander leaves. However, local Bukittinggi coriander leaves demonstrated greater antioxidant activity than the imported Egyptian leaves. GC–MS analysis revealed that the local Bukittinggi coriander leaf extract contained organic compounds such as 3,5-bis(1,1-dimethylethyl) phenol, phytol, and dl-α-tocopherol, unlike the imported Egyptian coriander leaf extract